The Change of Preference Priorities on Examination for Specialty in Medicine by Years of High Risky Medical Branches in Medical Malpractice - Kasap, Hüseyin; Akar, Taner; Demirel, Birol; Dursun, Ahmet Zahit; Sarı, Serhat; Özkök, Alper; Aydemir, Önder (The Bulletin of Legal Medicine, 2015)
Objective: Malpractice is defined as the illness going out of its normal course, delayed healing, death of a patient because of physicians unlawful and/or defective medical practice and treatment. The increase in the both criminal and compensation cases claiming malpractice have led the physicians to practice defensive medicine. Defensive medicine’s reflection to the "Examination for Specialty in Medicine" is that specialties withlower risk are preferred priorly.Materials and Methods: In this research it is aimed to demonstrate the change of preference priorities of specialties by physicians after the risk groups were determined relying on the ’Compulsory Liability Insurance Related to Medical Malpractice’, entered into force in 2010. According to this insurance, the group with the highest risk is 4th and the group with the lowest risk is the 1st. The base points of specialties according to 2009-2013 Examination for Specialty in Medicine (TUS) placement results were included to the research.Results: From 2009 to 2013 it was determined that second group’s base points increased gradually, third group remained stable and the fourth group decreased significantly.Conclusion: We believe that, the reason of the change of the priority of physicians is not only the rise of the violence of which the physicians are subjected to, but also, in spite of the increased number of claims braught and the amount of indemnity due to the higher risk of the medical application faults compared to other groups, the almost steady income of the physicians compared with that risks that take. While it is being discussed that defensive medicine is practiced more often each day, we demonstrated in this research that this situation is even reflected to the preferences of specialist candidates.Keywords: Medical malpractice, Defensive medicine, Examination for specialty in medicine.
Keywords: medical malpractice; defensive medicine; examination for specialty in medicine